2020
DOI: 10.3390/electronics9091433
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Virtualisation Techniques on Power System Control Networks

Abstract: Virtualisation is a concept successfully applied to IT systems. In this work, we analyse how virtualisation approaches, such as edge computing, brokerage and software-defined networking, can be applied in the area of electricity grid management and control systems. Power system information and communications technology is currently subject to significant changes. Networked power grid components including renewable energy units, electric vehicles and heat pumps need to be integrated into grid management systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Often, these applications are sandboxed, i.e., they are running in a closed environment and can then communicate only via these system interfaces, allowing for a controlled environment and thus assuring security and privacy guarantees. A more detailed overview of infrastructural research can be found in [52] (focusing on connectivity issues) and in [35] (focusing on interoperability frameworks).…”
Section: Quality Of Service Issuesmentioning
confidence: 99%
“…Often, these applications are sandboxed, i.e., they are running in a closed environment and can then communicate only via these system interfaces, allowing for a controlled environment and thus assuring security and privacy guarantees. A more detailed overview of infrastructural research can be found in [52] (focusing on connectivity issues) and in [35] (focusing on interoperability frameworks).…”
Section: Quality Of Service Issuesmentioning
confidence: 99%
“…Other publications in this context deal with topics like mathematical description and reliability assessment methods [2] and onboard fault diagnosis [3]. An approach for coping with these requirements by implementing a virtualization layer for power supply systems by using techniques known from information technology is presented in [4]. For aviation applications, the requirements for functional safety have always been even stricter.…”
Section: Introductionmentioning
confidence: 99%